Odpowiedź :
Odpowiedź:
Pc = 2Pp + 4Pb
a) Pp = a² = 2² = 4
Pb = a×h
Pc = 2×4 + 4×2×h
24 = 8 + 8h
16 = 8h
h = 2
b) Pp = [tex]\frac{a^{2} \sqrt{3} }{4}[/tex] = [tex]\frac{2^{2}\sqrt{3} }{4}[/tex] = [tex]\sqrt{3}[/tex]
Pb = a×h
Pc = 2[tex]\sqrt{3}[/tex] + 3×2×h
24 = 2√3 + 6h
6h = 24 - 2√3
h = [tex]\frac{24-2\sqrt{3} }{6}[/tex] /÷2
h = [tex]\frac{12-\sqrt{3} }{3}[/tex]
c) Pp = 6× [tex]\frac{a^{2} \sqrt{3} }{4}[/tex] = 6×[tex]\frac{2^{2}\sqrt{3} }{4}[/tex] = 6√3
Pc = 2×6√3 + 6×2×h
24 = 12√3 + 12h
12h = 24 - 12√3
h = [tex]\frac{24-12\sqrt{3} }{12}[/tex] /÷12
h = 12 - √3
Szczegółowe wyjaśnienie: